Intersectionality and Gendered Criminal Justice in South Asia: The Case of Pakistan - Jafri, Qamar Abbas (Women & criminal justice, 2025)
This study analyses intersectional perspective in relation to criminal legal justice in Pakistani society - a South Asian country with more than 220 million population. By drawing on insights from the women inmates and a criminal lawyer through qualitative interviews, the study probed the encounters of these women with criminal legal system and society. These women were incarcerated in drug-related offenses, murder, injury, and sex work. The study has found that social status identity (e.g., education and income), religious and gender identity of the women inmates experience the negative stereotyping, inadequate legal support, and discrimination in men’s dominated criminal justice system of Pakistan. The religious identity of the women inmates further overlaps in the legal system which can increase their vulnerability for discrimination in the criminal law that specifically deals with drug-related offenses. In relation to gender, women prisoners who are young and mothers with children allegedly incarcerated in murder were more vulnerable to patriarchal biasness and barriers of reintegration into family and community. The study has suggested skill-based education, establishment of free legal and reintegration service and oversight of police officials who register criminal cases against women offenders to prevent their religious and gender-based biasness while registering such cases.